Maximum Consumption Limits of Fish Catches Tainted by Lead (Pb) in 3 Fish Auction Markets (FAM) in Cilacap, Indonesia - Devi Fitriana; Sukmawati Sukmawati; Nur Rochman; Royani Royani; Oto Prasadi; Nurlinda Ayu Triwuri; Ilma Fadlilah (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2021)
Heavy metals produced by the industrial sector in Cilacap will contaminate the waters and impact the organisms in them, which will affect the condition of humans as consumers. The purpose of the importance of this research activity is to compare the type of fish and the value of heavy metal Pb with the quality standards of the Ministry of Environment No.51 of 2004, BPOM Regulation 2009 and SNI 7387 of 2009, as well as knowing the maximum consumption limit of consumption fish catches to control the pattern eat fish indicated heavy metals. The method used is a comparative description with survey techniques in 3 locations where fish auctions (FAM) and Pb level analysis using the AAS method. The types of fish with the highest level of consumption in Cilacap are kembung, tuna and tongkol. The Pb level of kembung, tuna and tongkol passes the threshold> 0.4 ppm from SNI 7387-2009 and BPOM 2009, namely 0.7 ppm, 2.9 ppm, and 2.3 ppm, respectively so it is essential to have a consumption limit per week through Tolerable Maximum Intake (MTI) with categories for adults and children for the consumption of each type of fish consumption. Research shows that the maximum consumption limit for adults in kembung, tuna and tongkol is 16.9 kg, 2.8 kg, and 9.2 kg, respectively. Meanwhile, the maximum limit of consumption of kembung, tuna and tongkol for children is 6.4 kg, 1 kg, and 2.9 kg, respectively.